Culture Wars under the Acropolis: The Ford Foundation and Greek Theater (1967-1974) - Zafiris Nikitas (Ex-centric Narratives: Journal of Anglophone Literature, Culture and Media, 2022)
This article examines the Ford Foundation grants awarded to Greek theater artists during the dictatorship (1967-1974) and the public discourse that emerged in the press in relation to the Foundation. The Ford Foundation sponsored a number of established playwrights and the Art Theater, while rejecting the applications of many other artists who failed to meet its criteria. The respective US funding created a wave of negative criticism (from artists that were rejected and other intellectuals) against the Foundation. This tendency reflected the anti-American sentiment that was evident during the dictatorship and posed questions on the relationship between culture and politics. The article looks into the documents of the Ford Foundation Archive (such as the approved and the rejected applications) and the articles in the Greek press in order to illuminate an intense culture war that posed pressing questions on the limits between the humanitarian efforts and the imperialistic aims of the US in Greece.